National Identity and Cultural Belonging in the Drawings of Kuwaiti Children (Al-Academy, 2026)
The study followed a descriptive-analytical approach to explore the perceptions of 15 children (aged 6 to 12) regarding national identity and cultural belonging in Kuwait. Data were collected through researcher observations and brief interviews while the children engaged with four main topics: the national flag, Liberation Tower, Al-Irada Square, and Al-Saif Al-Aamer Palace. Results from the test-retest reliability simulation and review by three experts indicated high reliability of the research tools. The findings revealed that five children expressed feelings of pride and belonging when drawing the national flag, while all 15 children focused on details when drawing Liberation Tower. At Al-Irada Square, seven children demonstrated emotional and social engagement, whereas nine children showed interest in heritage when drawing Al-Saif Al-Aamer Palace. These results suggest that diversifying subjects and artistic activities enhances visual perception, cultural awareness, and national belonging among children. The study recommends integrating national symbols, heritage, and architectural landmarks into education to promote these values.